Effect of processing methods on the nutrient, antinutrient, functional, and antioxidant properties of pigeon pea (Cajanus cajan (L.) Millsp.) flour - Abdulmajid Haji; Tilahun A. Teka; Tizazu Yirga Bereka; Tess Astatkie; Henock Woldemichael Woldemariam; Markos Makiso Urugo (Journal of Agriculture and Food Research)
Pigeon pea (Cajanus cajan) is an important grain legume in tropical regions, including Ethiopia. Yet its nutritional value is often limited due to the presence of antinutritional factors and limited studies on how traditional processing methods affect the nutritional, antinutritional, functional, and antioxidant properties of the flour. This study investigates how traditional processing methods—soaking, germination, cooking, and roasting—affect the nutritional, antinutritional, functional, and antioxidant properties of pigeon pea flour. Results indicated that processing methods significantly influenced the proximate composition; germination enhanced protein content from 23.50 % to 25.50 %, while cooking and roasting decreased it. Mineral content analysis revealed that calcium, iron, and zinc levels were generally reduced, with cooking leading to the greatest decreases in mineral concentrations. All processing methods effectively reduced antinutritional components, with germination achieving the most substantial reductions in phytic acid and tannins. Functional properties were also affected: bulk density decreased across all methods, while water and oil absorption capacities increased, particularly in germinated flour. Germination notably enhanced total phenolic content from 209.61 to 252.60 mg/100 g and antioxidant activity, as measured by DPPH and FRAP values. Conversely, soaking, cooking, and roasting decreased phenolic content and antioxidant capacity. Overall, while germination improved the nutritional and antioxidant profiles of pigeon pea flour, other processing methods significantly diminished these beneficial properties, highlighting the importance of processing in enhancing the nutritional value of pigeon peas.